Resource selection and survival of plains sharp‐tailed grouse at a wind energy facility - Carly S. Kelly; Chad W. LeBeau; Jeffrey L. Beck; Alex Solem; Hilary Morey; Kurt T. Smith (Ecosphere)
Abstract As the demand for wind energy development increases across much of the Great Plains region, there is a need to understand how this type of energy generation may impact wildlife. Due to their extensive range across areas with high wind resources, plains sharp‐tailed grouse (Tympanuchus phasianellus jamesiTympanuchus phasianellus jamesi) represent a valuable species to evaluate how selection and survival are associated with existing wind energy infrastructure. We used spatial and demographic data collected from radio‐marked female sharp‐tailed grouse to evaluate resource selection (nest, brood‐rearing, and breeding season) and survival (nest and female) near existing wind energy infrastructure during the April to August breeding season over a 3‐year period from 2020 to 2022 in northeastern South Dakota, USA. We monitored 119 GPS‐marked females captured at eight leks over the study period. We did not find evidence that females selected nest sites in relation to wind energy infrastructure but found that females with broods and females during the breeding season (April–August) avoided areas near high densities of wind turbines within 1.0 and 5.0 km of their home range, respectively. We found consistent selection for lower lengths of transmission lines across all life stages at the home range scale. We did not detect an effect of wind energy infrastructure on nest or female survival. Based on the results of our study, limiting the siting (the process of selecting the optimal location for a project and the associated features) of wind turbines within 5.0 km of sharp‐tailed grouse breeding habitat may represent an important siting tool to minimize avoidance of otherwise suitable habitats.